The design and implementation of the software tracking cervical and lumbar vertebrae in spinal fluoroscopy images. (11th September 2017) - Savareh, Behrouz Alizadeh; Sadat, Yousef; Bashiri, Azadeh; Shahi, Mehraban; Davaridolatabadi, Nasrin
Aim: Manual analysis of neck kinematics is usually associated with measurement errors and it requires the use of software capabilities. Considering laboratory usage, software has been developed to solve the associated problems.Materials & methods: Fluoroscopic images taken from 78 women were used to design and evaluate the performance of the software. The software was implemented using C# language, according to the case-based reasoning technique.Results: The viewpoints of experts suggest accuracy of the software in tracking and calculations, which meets their information requirements.Conclusion: Using the software could help physiotherapists to accomplish their work in decreased time and with improved accuracy. Lay abstract: Manual analysis of neck kinematics usually suffers from measurement errors and requires the use of the software capabilities. In this research article, a software has been developed to solve this problem. The software is implemented using C# language, according to the case-based reasoning technique. Experts using the software suggested its accuracy in tracking and calculations, which met their information requirements. Using the software could help physiotherapists to accomplish their work in decreased time and improved accuracy. However, further research is to confirm these results.